Qualitative Human Chorionic Gonadotropin Testing in Vaginal Fluid for Diagnosis of Preterm Premature Rupture of Membrane - Mehra, Reeti; Huria, Anju; Mahaur, Beena (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v4i2.5043 NJOG 2010 Jan-Feb; 4(2): 28-31